Produksi Furfural Dari Tandan Kosong Sawit Dengan Berbagai Perlakuan Awal - Yasinta Lola Iriadi; Said Zul Amraini; Evelyn Evelyn (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Furfural is one of the furan derivatives that is widely used as a solvent in the extraction of lubricating oils and natural oils. Furfural can be made from materials containing pentose such as palm oil empty fruit bunches. The purpose of this study is to examine the utilization of palm oil empty fruit bunches as a raw material in the manufacture of furfural. There are three stages carried out in this study, pretreatment, hydrolysis, and distillation. The pretreatment process used 9% H2SO4, 9% NaOH, and 50% ethanol as solvent, which was cooked at temperature 120oC for 1 hour, 1.5 hours and 2 hours. The results showed that acid pretreatment process with 9% H2SO4 was the best process in producing furfural. Hemicellulose from palm oil empty fruit bunches can produce pentose and furfural which can be used as industrial raw materials. The highest yield of furfural obtained from pretreatment using 9% H2SO4 with reaction time 2 hours at 8.64% and the lowest yield of furfural yield obtained from pretreatment using 9% NaOH with 1 hour reaction time at 1.06%.Keywords : furfural, palm oil empty fruit bunches, pretreatment